Cutting temperature in high speed milling of silicon carbide using diamond coated tool - Iqbal, Mohammad; Konneh, Mohamed; Ani, Mohd Hanafi; Abdallah, Kassim Abdulrahman; Binting, Muhammad Faruq (Institute of Technology and Research, 2015)
The present research studies the high speed milling process of Silicon Carbide, using diamond coated tool. The effect of machining parameters such as cutting speed, feed rate and depth of cut on the cutting temperature were investigated. The experiments were conducted under dry condition with two flute diamond coated flat end-mill of diameter 2 mm, using different spindle speeds (between 30,000 and 50,000 rpm), different feed rates (between 6 and 60 m/min), and different depth of cuts (between 0.05 and 0.1 mm). Experimental results indicated that all the milling parameters influence the cutting temperature. Cutting temperature increases with the increase of cutting speed at higher depth of cut, but decreases at lower depth of cut. Increasing feed rate will increase cutting temperature at any conditions. Meanwhile, increasing depth of cut will increase cutting temperature at lower feed rate, but decrease cutting temperature at higher level of feed rate. As the conclusion, the combination of high spindle speed with low feed rate and low depth of cut minimizes cutting temperature developed in high speed milling of SiC with diamond coated tool.